2005
DOI: 10.1051/apido:2005043
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants of bee products

Abstract: -Bee products can be contaminated from different sources. The contamination can arise from beekeeping practices or from the environment. Environmental contaminants are covered in the first part of the review. They are: the heavy metals lead, cadmium and mercury, radioactive isotopes, organic pollutants, pesticides (insecticides, fungicides, herbicides and bactericides), pathogenic bacteria and genetically modified organisms. The second part of the review discusses contaminants from beekeeping. The main ones ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
427
0
39

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(477 citation statements)
references
References 60 publications
11
427
0
39
Order By: Relevance
“…Others have also found elevated toxic metals in bee pollen [12][13][14][15], but there have been few publications dealing with bee bread contamination. Our results showed that in both bee products As was present in highest concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Others have also found elevated toxic metals in bee pollen [12][13][14][15], but there have been few publications dealing with bee bread contamination. Our results showed that in both bee products As was present in highest concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As no single explanation for the extensive colony losses has been identified, it is concluded that many biological and environmental stressors, acting alone or in combination, can lead to premature colony mortality (vanEngelsdorp et al 2009, Genersch 2010. Along with bee diseases, many problems in beekeeping are caused by chemicals used against honey bee pathogens, whose appliance is accompanied by side effects on bees and brood (Pettis et al 2004a, 2004b, Loucif-Ayad et al 2008, contamination of bee products (Bogdanov 2006) and health risk to beekeepers and bee product consumers (Stanimirovic et al 2005, Stevanovic et al 2008, Radakovic et al 2013. Therefore, it would be benefitial if some harmless naturalbased supplements could provide maintaining healthy and strong honey bee colonies and help in prevention of their mortality.…”
Section: Honey Bees Apis Mellifera L (Hymenopteramentioning
confidence: 99%
“…Apart from essential minerals, bee pollen may also contain contaminants as it is exposed to different contamination sources in its environment (Bogdanov, 2006;Wiest et al, 2011). The indiscriminate use of pesticides on crops and the industrial contamination of soils, rivers and lakes introduce some heavy metals, harmful to living organisms, into agricultural ecosystems.…”
Section: Introductionmentioning
confidence: 99%